False Recognition of Emotionally Categorized Pictures in Young and Older Adults - Zheng, Zhiwei; Lang, Minjia; Wang, Wei; Xiao, Fengqiu; Guo, Shuhan; Li, Juan (Frontiers in Psychology, 2019)
Normal aging is associated with the shift in motivational priorities from knowledge acquisition to emotion regulation. Current evidence indicates an age-related increase in preferences for positive over negative stimuli in true memory. In the present study, using the categorized pictures paradigm, we investigated whether older adults would exhibit a greater increase in false memory for positive versus negative lures, compared with young adults. We also examined the association of executive functioning with the preferences for positive over negative pictures in false recognition memory. A total of 27 young and 26 older adults studied emotional pictures from various categories during encoding and subsequently completed an old/new recognition test. In addition, all participants completed the executive functioning tests. The results revealed that both older and young adults showed higher rates of false recognition for positive pictures compared with negative pictures; no significant group by valence interaction was observed. Trail making scores were negatively correlated with positive processing preferences in false recognition rates in older but not young adults. These findings suggest that false recognition memory exhibits preferences toward positively valenced stimuli in both young and older adults. Cognitive control processes are necessary for older adults to distort memory in emotionally gratifying ways.